INTERVENTION OF 5-FINGER HYPNOTIC RELAXATION TECHNIQUE IN COMPREHENSIVE MIDWIFERY CARE FOR FOR A MULTIPAROUS WOMAN WITH PREGNANCY-RELATED ANXIETY - Wardany, Marzita; Nursifa, Niknik; Sri Mujiwati; Sri Lestari, Endah (STIKes Budi Luhur Cimahi, 2024)
During the third trimester of pregnancy, women often experience various discomforts, including anxiety. One non-pharmacological treatment to alleviate this anxiety is the Five-Finger Hypnosis technique. At Clinic